Geographic knowledge infrastructure applications to territorial intelligence and smart cities - Laurini, Robert (London Elsevier, 2017)
Geographic Knowledge Engineering: Applications to Territorial Intelligence and Smart Cities studies the specific nature of geographic knowledge and the structure of geographic knowledge bases. Geographic relations, ontologies, gazetteers and rules are detailed as the basic components of such bases, and these rules are defined to develop our understanding of the mechanisms of geographic reasoning. The book examines various problems linked to geovisualization, chorems, visual querying and interoperability to shape knowledge infrastructure for smart governance.--Provided by publisher.
From geodata to geographic knowledge -- Knowledge representation -- Towards geographic knowledge systems -- Geographic objects -- Geographic relations -- Geographic ontologies -- Complex geographic objects and structures -- Gazetteers and multilingualism -- Geographic knowledge discovery and data mining -- Geographic applicative rules -- Geovisualization and chorems - GKS: querying and interoperability -- Conclusion: knowledge as infrastructure for smart governance.
Includes bibliographical references
Electronic reproduction.
Keywords: Geographic information systems; Electronic books